2008
DOI: 10.1177/1077559507310612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Foster Parent Training Intervention on Placement Changes of Children in Foster Care

Abstract: Placement disruptions undermine efforts of child welfare agencies to promote safety, permanency, and child well-being. Child behavior problems significantly contribute to placement changes. The aims of this investigation were to examine the impact of a foster parent training and support intervention (KEEP) on placement changes and to determine whether the intervention mitigates placement disruption risks associated with children's placement histories. The sample consisted of 700 families with children between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
158
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 29 publications
9
158
0
6
Order By: Relevance
“…Studies have found that participation in these interventions is associated with fewer negative exits from foster placements and greater permanency. 8,[15][16][17] Interestingly, 2 of these studies found that the interventions moderated the association between placement instability and permanency outcomes. 15,17 Another study found that placement changes predicted dysregulation in cortisol for the control group only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that participation in these interventions is associated with fewer negative exits from foster placements and greater permanency. 8,[15][16][17] Interestingly, 2 of these studies found that the interventions moderated the association between placement instability and permanency outcomes. 15,17 Another study found that placement changes predicted dysregulation in cortisol for the control group only.…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17] Interestingly, 2 of these studies found that the interventions moderated the association between placement instability and permanency outcomes. 15,17 Another study found that placement changes predicted dysregulation in cortisol for the control group only. 18 Our study adds to the growing body of literature by examining the impact of a child-focused intervention on permanency and placement outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to various, mainly quantitative studies, frequently cited reasons for breakdown that are attributed to the foster child include: behavioural and attachment problems on the part of the child (James, 2004;van Santen, 2013;Vanderfaeillie et al, 2008), divided affiliations and loyalties (Blandow, 2004;van Santen, 2013), and school problems (Ekins, 2009;van Santen, 2013). Reasons for breakdown attributed to the foster parents include: subjecting the foster child to physical or sexual abuse (James, 2004;Price et al, 2008;Vanderfaeillie et al, 2008), being unable to cope (Andersen, 2014;Gehres, 2007), demanding an exclusive relationship (Gehres, 2007), suffering too much stress from the behaviour of the foster child (James, 2004), being affected by critical life events (Ekins, 2009;James, 2004), and not receiving enough support from the social network (Ekins, 2009;Price et al, 2008;van Santen, 2013). Factors relating to the system are relatively rarely identified as a cause of breakdown, and little attention is paid to the interaction between the different actors involved in the process (birth family, foster family, foster child, foster siblings, representatives of the authorities, social workers, etc.).…”
Section: System Logic Channels Attention To the Child's Behaviourmentioning
confidence: 99%
“…Factors relating to the system are relatively rarely identified as a cause of breakdown, and little attention is paid to the interaction between the different actors involved in the process (birth family, foster family, foster child, foster siblings, representatives of the authorities, social workers, etc.). References are made to emerging difficulties and "rivalries between family systems" (van Santen, 2013), unclear arrangements and poorly implemented support services on the part of the child welfare system (Ekins, 2009;Gehres, 2007;Price et al, 2008), and the insufficient availability of information about the foster child (Kalland & Sinkkonen, 2001). …”
Section: System Logic Channels Attention To the Child's Behaviourmentioning
confidence: 99%
“…11 We used these data to evaluate trends and case outcomes. 13 we refer to the first 4 outcomes as "positive exits" because these are desirable permanency outcomes in child welfare.…”
Section: Data Sourcesmentioning
confidence: 99%